Direito humano e fundamental ?? sa??de como determinante do meio ambiente ecologicamente equilibrado e do desenvolvimento sustent??vel - Del Rio, Raquel Moreira de Oliveira (2015)
This study aims to analyze the right to health and the right to the environment, observing the importance of reaching an ecologically balanced environment and sustainable development so it can provide quality of life and adequate health care to citizens, actualizing human rights. The research bases in the 1988???s Federal Constitution, which qualifies health and ecologically balanced environment as a fundamental right and duty of all citizens and duty of the State and the community to protect and preserve, in addition to their interdependence with human rights internationally recognized. The dignity of the human person is guaranteed by a set of rights and guarantees of the human being, which reflects the actual human rights, and by being universal, indivisible and interdependent are recognized globally. The function of the right to health intent to qualify the society life conditions, which depends on the ecological balance of the environment, essential to a healthy quality of life. In other words, maintaining the environment balanced, there will be an improvement in the health of each individual. The research is conducted from the historical evolution of the fundamental right to health as well as their protection through international treaties and conventions that deal with the environment and human rights. The intersection of the right to health with the environment, conceptual aspects, principles ruling the environment and environmental policies. The intergenerational responsibility and analysis of legislation and constitutional foundation of health and the environment. Addresses the legalization of health demonstrating, through law cases, the guarantee of constitutional law where public policies faild. Anyway, the work highlights the importance of achieving a balanced environment to promote and qualify the health and suport the welfare of society and future generations, with the realization of human person fundamental rights.